From “Countering” To “Constructing” Russian Threats in Mikheil Saakashvili’s Georgia - A. T. Sikharulidze (Международная аналитика, 2022)
This paper looks at the securitization process that took place during M. Saakashvili’s time as President of Georgia. It argues that, in order to overshadow political misdeeds and non-democratic state-policy as a whole, M. Saakashvili and his political allies used “constructed” Russian threats to discredit and marginalize opponents. Furthermore, M Saakashvili’s regime tended to restrict freedom of speech, civil liberties and other democratic rights by referring to non-existent constructed threats from the Moscow. Through security dimension, Russia poses a menace to Georgia’s territorial integrity, sovereignty and Western aspirations. But at the time of M. Saakashvili’s presidency it has been turned into a political tool to be used against opponents. This paper off ers a scholarly debate on the issue. Finally, it gives a case-by-case analysis of the most crucial happenings that explain “how” and “why” Russia has been securitized.